2018
DOI: 10.1016/j.compstruct.2018.01.084
|View full text |Cite
|
Sign up to set email alerts
|

Insights into complex rheological behaviour of carbon fibre/PEEK from a novel numerical methodology incorporating fibre friction and melt viscosity

Abstract: Insights into complex rheological behaviour of carbon fibre/PEEK from a novel numerical methodology incorporating fibre friction and melt viscosity. Composite Structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
3
11
0
Order By: Relevance
“…the initial behaviour is not purely elastic). Also, the fibre friction and fibre-melt interaction are highlighted in the section 4.2 for interpretation which are consistent with the findings of Deignan et al [41]. This suggests that the commonly used phenomenological approaches such as standard linear visco-elastic models and micromechanics based models such as those from Christensen [28] or Pipes et al [29] may fail to capture the observed behaviour.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…the initial behaviour is not purely elastic). Also, the fibre friction and fibre-melt interaction are highlighted in the section 4.2 for interpretation which are consistent with the findings of Deignan et al [41]. This suggests that the commonly used phenomenological approaches such as standard linear visco-elastic models and micromechanics based models such as those from Christensen [28] or Pipes et al [29] may fail to capture the observed behaviour.…”
Section: Discussionsupporting
confidence: 79%
“…This seem to be related to the microstructure of the prepreg. Deignan et al [41], working on fibre reinforced thermoplastic melts, have suggested that the resistive forces between two fibres increases with shear rate.…”
Section: Effect Of the Applied Loading Ratementioning
confidence: 99%
“…In addition, the curves of neat PVDF were well superimposed into a master curve, suggesting a simple rheological behavior. As far as the curves of the PVDF composites were concerned, they all displayed a significant divergence (especially in the middle and end regions of the curves) with increasing GNP content, which revealed the complexity in rheological behavior of the composites …”
Section: Resultsmentioning
confidence: 99%
“…As far as the curves of the PVDF composites were concerned, they all displayed a significant divergence (especially in the middle and end regions of the curves) with increasing GNP content, which revealed the complexity in rheological behavior of the composites. [47] 3.3 | Thermal conductivity and in situ temperature measurement…”
Section: Dynamically Rheological Analysismentioning
confidence: 99%
“…12 However, the processability of PEEK is somewhat difficult, owing to its high melting temperature. 13 In this respect, poly(ethylene 2,6-naphthalate) (PEN) may become an ideal matrix of CFRCs owing to its favorable processing conditions and excellent performance.…”
Section: Introductionmentioning
confidence: 99%